Morphometric Description of Cyclospora-like Coccidian in a Stray Dog (Carnivora: Canidae) from Nepal - Adhikari, Roshan Babu; Ghimire, Tirth Raj (Journal of Agriculture and Forestry University, 2025)
Cyclospora spp. causes intestinal cyclosporiasis and exists as a globally emerging pathogen in humans. However, the infection has also been reported from various animal hosts, including domestic canids. Very few articles have highlighted the presence of this coccidian in dogs, but interestingly, in each case; the oocyst morphology resembles that of human strains (C. cayetanensis). Here within, we have addressed a new description of the oocyst morphology of Cyclospora-like coccidian reported in the feces of a young female free-ranging street dog in Lalitpur Metropolitan City in central Nepal. Sporulation of oocyst is exogenous and completed within a week at 28°C with a 1:4 ratio in a 2.5% potassium dichromate solution. A mature oocyst was spherical, measuring 22.5 μm × 21.5 μm (22-23 μm × 21-22 μm, n = 10), with a shape index of 1.03 (1.0–1.05), an oocyst thickness of 0.5 μm, and a smooth and bilayered oocyst wall. Similarly, the oocyst was dizoic and was broadly elliptical sporozoites (average size: 9.9 μm × 8.3 μm, shape index: 1.2) with an inconspicuous nipple shaped stieda body and sporocyst residuum.